Uang dan Mekanisme Bunga: Konsep, Definisi, serta Contoh dalam Sistem Ekonomi Modern - Vina Rakhmawati; Eka Nurfadila; Gama Pratama (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to examine the concepts, definitions, and examples of money and the mechanism of interest in the modern economic system, from both conventional and Islamic perspectives. Money functions as a medium of exchange, a store of value, a unit of account, and a standard of deferred payment, making it an essential element of economic activity. The development of financial technology has transformed the form and function of money into more efficient and accessible digital systems. In the conventional economic system, interest serves as a key monetary policy instrument to regulate the money supply, inflation, and economic growth. However, the interest system has been criticized for potentially creating social inequality. In contrast, Islamic economics rejects interest as it contains elements of riba and replaces it with a fair profit-sharing system based on partnership. This study uses a qualitative method with a literature review approach based on Indonesian journals and academic books published between 2019 and 2025. The results show that both conventional and Islamic systems play a vital role in maintaining fairness and stability in the modern economy.